Psychometric evaluation of the Spanish version of the therapeutic communication scale in nursing students - Jaime Carballedo-Pulido; Bárbara Hurtado-Pardos; Juan Roldán-Merino; Marta Berenguer-Poblet; Manuel Tomás-Jiménez; Montse Lamoglia-Puig; Emma Gómez Fernández; Marta Domínguez-del-Campo; Carla Otero-Arús; Mariona Farrés-Tarafa; Susana Santos-Ruiz (PLoS ONE, 2025)
Background Therapeutic communication is a core component of person-centered nursing care. Despite its clinical relevance, few validated instruments exist in Spanish that objectively assess this competence in undergraduate nursing students. Objective This study aimed to adapt and validate the Spanish version of the Therapeutic Communication Scale in Nursing Students (TCS-NS), originally developed by Han et al. (2024), and to examine its psychometric properties in a Spanish-speaking context. Methods A psychometric study was conducted in two phases: (1) translation and cross-cultural adaptation following international guidelines, including expert panel review and pilot testing; and (2) psychometric evaluation with a sample of 468 nursing students. Construct validity was assessed using confirmatory factor analysis (CFA), and reliability was examined via Cronbach’s alpha, McDonald’s omega, composite reliability, and test-retest stability (ICC). Results The CFA supported the two-factor structure of the TCS-NS and indicated good model fit (CFI = .963; TLI = .954; RMSEA = .053; SRMR = .044). Internal consistency was adequate for the total scale (α = .880; ω = .884), and composite reliability was high (.936). The intraclass correlation coefficient for the total score was.696 (95% CI:.605–.766). Conclusions The Spanish version of the TCS-NS is a valid and reliable instrument for assessing therapeutic communication skills in nursing students. Its use may contribute to the objective evaluation of communication competence in educational interventions and research.